SOME REFLECTIONS ON KAFKA AND THE LAW (Journal of Contemporary Philology, 2021)
This paper is a follow-up to a research conducted for the purposes of the workshop entitledFranz Kafka: from the ‘Penal Colony’ to ‘Process held at Iustinianus Primus Faculty of Law as a part of the project Critical Re-Examination of Law. The paper encompasses an analysis of the works by Franz Kafka from a point of view that relates literature with the concept of Law. This paper draws on the philosophical reflections of Teodor Adorno, Giles Deleuse and Félix Guattari, as well as on Giorgio Agamben’s philosophical paper dedicated to Kafka, and aims at offering new perspectives to the interpretation of Kafka’s work which situate the writer the in the context of the contemporary dynamic tenndecies withinthe social and the political order.
Keywords: literary machine; law; guilt; punishment; language